Dari Mitos Menstrual Taboo Ke Dunia Kecantikan dan Fashion - Yuswati, Yuswati (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
Menstrual Taboo is a never ending phenomenon. We can study about it from different points of view: medical, psychological, anthropological, mythological, theological as well as ideological perspectives. Talking about the popular myth of menstrual taboo, there are